Pertumbuhan Ekonomi Dan Dana Alokasi Umum Terhadap Anggaran Belanja Modal - Rinto Hasrat Budi Lase; Febryandhie Ananda (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to determine the effect of Economic Growth and General Allocation Fund on the Capital Expenditure Budget in part and simultaneously from districts/cities in West Sumatra Province for the 2018 – 2021 period. The data used are secondary data from the Central Statistics Agency (BPS) of West Sumatra, quantitative collection data methods and analysis techniques used are panel data regression. Before that, a classical assumption test was carried out to find out a good model in statistics, then a hypothesis test was carried out using the t test and the f test. The research showed some of the influence of Economic Growth (X1) and the General Allocation Fund (x2) on the Capital Expenditure Budget (Y). The result found is that Economic Growth (X1) has not had a positive effect on the Capital Expenditure Budget (Y) while the General Allocation Fund (X2) has a positive effect on the Capital Expenditure Budget (Y).